Optimal compensation contracts when managers can hedge - Gao, Huasheng (Journal of Financial Economics, 2010)
This paper examines optimal compensation contracts when executives can hedge their personal portfolios. In a simple principal-agent framework, I predict that the Chief Executive Officer's (CEO's) pay-performance sensitivity decreases with the executive-hedging cost. Empirically, I find evidence supporting the model's prediction. Providing further support for the theory, I show that shareholders also impose a high sensitivity of CEO wealth to stock volatility and increase financial leverage to resolve the executive-hedging problem. Moreover, executives with lower hedging costs hold more exercisable in-the-money options, have weaker incentives to cut dividends, and pursue fewer corporate diversification initiatives. Overall, the manager's ability to hedge the firm's risk affects governance mechanisms and managerial actions.